JUSTIFIKASI KEBUTUHAN TENAGA KERJA BERKEBUTUHAN KHUSUS DI BERBAGAI INDUSTRI GUNA MEMENUHI UNDANG-UNDANG NO.8 TAHUN 2016 BERBASIS KERANGKA CDIO - Innas Rovino Katuruni; Sri Isti Untari; Maria Nino Istia (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The issue of disability is now an interesting issue to discuss. One of them is about workers with special needs. This has been regulated in law, but it is feared that many people do not know or even apply these regulations. To meet these standards, education for Citizens with Special Needs is also of good quality. One of the educational frameworks that is currently being developed, especially in vocational education, is using the CDIO framework. The aim of this research is to identify to what extent the qualities needed by people with disabilities to be accepted in the world of work. To achieve this, in-depth interviews were conducted with parties deemed qualified to represent a small part of the world of work. From the results obtained, it is hoped that graduates will be able to achieve points 3 to 4. It is hoped that the results of this research can provide input, especially for education providers for people with disabilities, so that they can achieve what the industry needs.